Analisis dan Perancangan Sistem Informasi Panduan Kesehatan Balita - Lestari, Merrryana; Sediyono, Eko (Asosiasi Doktor Sistem Informasi Indonesia, 2021)
Immunization, nutritional support for food vitamins and nutritional content from food are important components to support good children's growth and development. However, the number of malnutrition and malnutrition in Indonesia is still high, causing many children under five to experience stunting during the golden age. Through this research, analysis and design of mobile-based information systems that can be accessed anywhere and anytime as needed is carried out. The design of this information system can be used as a guide for young mothers regarding child health information needed, especially during the growth and development period of toddlers by monitoring growth curves and providing health recommendations through the calculation of the Body Mass Index (BMI) in toddlers and can also be used as a reminder and recording of immunization data in children under five.